Accessible Communication A Cross-country Journey - Perego, Elisa (Frank & Timme, 2020)
Easy-to-Understand (E2U) text practices enable and facilitate accessible communication. E2U refers both to Plain and to Easy Language. These two powerful methods of language and content comprehension enhancement are illustrated through several examples in English, starting from the seminal role of the Anglophone world in promoting plain and lucid style. Originally implemented in written texts, today the employment of these simplified language varieties should infiltrate new communication services that are more complex and multifaceted. Thanks to the EASIT project, the integration of E2U strategies into a selection of audiovisual services is being successfully researched. After advancing simplification proposals in the area of subtitling and audio description, Elisa Perego reports on the results of a cross-country survey conducted during the initial stages of the EASIT project: She pinpoints the background, activity, and training experience of those who currently work in the sector of E2U in Europe, and identifies the skills and the competences of, as well as a training path and materials for, future hybrid professionals.